Trap Inlaid Cationic Hybrid Composite Material for Efficient Segregation of Toxic Chemicals from Water. (30th May 2022) - Fajal, Sahel; Mandal, Writakshi; Mollick, Samraj; More, Yogeshwer D.; Torris, Arun; Saurabh, Satyam; Shirolkar, Mandar M.; Ghosh, Sujit K.
Abstract: Metal‐based oxoanions are potentially toxic pollutants that can cause serious water pollution. Therefore, the segregation of such species has recently received significant research attention. Even though several adsorbents have been employed for effective management of chemicals, their limited microporous nature along with non‐monolithic applicability has thwarted their large‐scale real‐time application. Herein, we developed a unique anion exchangeable hybrid composite aerogel material (IPcomp‐6), integrating a stable cationic metal–organic polyhedron with a hierarchically porous metal–organic gel. The composite scavenger demonstrated a highly selective and very fast segregation efficiency for various hazardous oxoanions such as, HAsO4 2−, SeO4 2−, ReO4 −, CrO4 2−, MnO4 −, in water, in the presence of 100‐fold excess of other coexisting anions. The material was able to selectively eliminate trace HAsO4 2− even at low concentration to well below the As V limit in drinking water defined by WHO. Abstract : A hybrid composite aerogel material has been systematically fabricated by encapsulating an active nanosized cationic metal–organic polyhedron in a stable hierarchical porous metal–organic gel matrix. The hybrid aerogel demonstrated efficient and highly selective extraction of metal‐based toxic oxoanions in both batch and dynamic column exchange experiments from simulated industrial wastewater and natural ground water systems.